Legal Protection for Children Out of Wedlock: Ensuring the Best Interests of Children Through Judge Decisions - Rohmawati, Rohmawati; Siddik, Syahril (Universitas Islam Negeri Raden Intan Lampung, 2022)
This article examines the protection of the rights of children out of wedlock in the Religious Courts. The ambiguity of the concept of the best interests of the child has prompted judges to interpret this concept to realize legal protection for children out of wedlock. This study reveals the application of the principle of best interests for children by Religious Court judges in protecting children out of wedlock. This study uses a case approach and legal philosophy. The results of this study indicate that the Religious Courts, in determining the origin of children, generally protect the rights of children out of wedlock proportionally. In the best interests of the child, the judges grant recognition of the child and provide a limited legal relationship for an illegitimate child with his biological father. The existence of this legal relationship has provided legal certainty regarding the status of children out of wedlock as biological children of both parents; so that the children have human dignity (hifẓ al-‘irḍ). In addition, judges have realized distributive justice that provides benefits for children out of wedlock, without ignoring the norms of Islamic law regarding the purity of lineage, through the granting of living rights for the survival of children (hifẓ al-nafs), spiritual development (hifẓ al-din), education a proper will (hifẓ al-'aql), and a mandatory will from his father (hifẓ al-māl).